Martian atmospheric data assimilation with a simplified general circulation model: Orbiter and lander networks - Lewis, SR; Read, P; Collins, M (1996)
A meteorological data assimilation scheme for the martian atmosphere has been implemented and tested, based on techniques used in the current operational scheme for weather forecasting at the U.K. Meteorological Office. The scheme has been interfaced with a range of simple models and with the martian GCM currently under simultaneous development at Laboratoire de Météorologie Dynamique du CNRS in Paris and at Oxford. As well as the interpretation of data from any future spacecraft, the assimilation scheme may be used for comparisons between different models, for model validation using earlier martian data, and for data impact studies to assist in planning new missions. Despite proposed new missions to Mars, observations of the atmosphere of Mars in the near future are still likely to be very sparse compared to those of the Earth (perhaps comprising a single orbiter and a few surface stations at any one time) and the scheme has been adapted with this in mind. Twin model experiments are conducted in which simulated observations are generated from a second model started from different initial conditions. Such experiments reveal the importance of surface pressure measurements (in combination with an accurate topographic map, such as will be available from laser altimetry) in the determination of the amplitude of large-scale atmospheric waves. It is shown that atmospheric temperature profiles from a remote-sensing instrument on a polar orbiting satellite combined with simultaneous surface pressure observations at a limited number of sites, as planned for the InterMarsNet mission, is a useful scenario for data assimilation. Copyright © 1996 Elsevier Science Ltd.